Getting Across the Plasma Membrane and Beyond: Intracellular Uses of Colloidal Semiconductor Nanocrystals - Luccardini, Camilla (Hindawi Publishing Corporation, 2007)
Semiconductor nanocrystals (NCs) are increasingly being used as photoluminescen markers in biological imaging. Their brightness, large Stokes shift, and high photostability compared to organic fluorophores permit the exploration of biological phenomena at the single-molecule scale with superior temporal resolution and spatial precision. NCs have predominantly been used as extracellular markers for tagging and tracking membrane proteins. Successful internalization and intracellular labelling with NCs have been demonstrated for both fixed immunolabelled and live cells. However, the precise localization and subcellular compartment labelled are less clear. Generally, live cell studies are limited by the requirement of fairly invasive protocols for loading NCs and the relatively large size of NCs compared to the cellular machinery, along with the subsequent sequestration of NCs in endosomal/lysosomal compartments. For long-period observation the potential cytotoxicity of cytoplasmically loaded NCs must be evaluated. This review focuses on the challenges of intracellular uses of NCs.